Ceramic technology, environment & residential mobility in small scale groups: preliminary trends from north Patagonia, Argentina - Franchetti, Fernando Ricardo (2013)
The purpose of this paper is to analyze four ceramic assemblage sets and discuss the relationship between ceramic investment, environment, and strategies of mobility among Late Holocene hunter-gatherers in southern Mendoza. The analyzed assemblages come from the areas of Llancanelo, Atuel Medio, Rio Grande, and surface materials from Volcán Overo. Different attributes of the archaeological ceramic like wall thickness, temper size, and surface preparation, enable us to evaluate the residential mobility of local human populations. Trends withineach assemblage and among sets can be drawn from the study. Finally, the results point to heterogeneity between the relationship of the concept of investment in each locality and its implications for making inferences about hunter-gatherer mobility.